Adsorption of perfluorosulfonic acids (PFSAs) on an ultrafine potato peel waste grafted β-cyclodextrin (UFPPW-β-CD) (2024)
Per- and polyfluoroalkyl substances are widely used in various consumer products. However, these compounds can cause various harm to the environment and health. Considering the high chemical stability, these compounds are not completely removed from the aqueous environment, and consequently, recent studies have detected their presence in water bodies. In this scenario, biomass-based adsorbents are promising. β-cyclodextrin (β-CD) was grafted in an ultrafine potato peel waste (UFPPW) to produce a novel, efficient, and sustainable adsorbent (UFPPW-β-CD) that was used to remove three different perfluorosulfonic acids (PFSAs) from water. The efficient grafting was proved by several characterization techniques, which also demonstrated the main UFPPW-β-CD features. The UFPPW-β-CD was efficient for all PFSAs (perfluorohexanesulfonic acid (PFHxS), perfluoropentanesulfonic acid (PFPeS), and perfluorobutanesulfonic acid (PFBS)), with removal percentage higher than 74 %. The increase in the Csingle bondF chain of PFSAs favored the adsorption due to the host–guest hydrophobic interactions between the Csingle bondF chains of the adsorbates and the hydrophobic cavity of the β-CD. Removal percentages and adsorption capacities at pH 3.0 were 74.6 % (49.92 µg g−1) to the PFBS, 82.6 % (65.66 µg g−1) to the PFPeS, and 90 % (100.89 µg g−1) to the PFHxS. The kinetic followed the General order model, while the equilibrium agreed with the Sips isotherm. The adsorption capacity increased with the increase in the Csingle bondF chain of the adsorbate, but the adsorption rate followed the opposite trend. PFSAs adsorption on the UFPPW-β-CD adsorbent was favorable and exothermic. UFPPW-β-CD could be used seven times, keeping its maximum adsorption capacity constant using ultrasound-assisted desorption. It can be concluded that UFPPW-β-CD is a sustainable adsorbent to uptake PFSAs from water, and this process is dependent on the size of the Csingle bondF chains.